2019
DOI: 10.1140/epjc/s10052-019-7543-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular $$\Xi _{bc}$$ states from meson–baryon interaction

Abstract: We have studied the meson-baryon interaction in coupled channels with the same quantum numbers of Ξ bc . The interaction is attractive in some channels and of sufficient intensity to lead to bound states or resonances. We use a model describing the meson-baryon interaction based on an extrapolation of the local hidden gauge approach to the heavy sector, which has been successfully used in predicting Ω c and hidden charm states. We obtain many states, some of them narrow or with zero width, as a consequence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…Then two comments are in order: the first one is that when dealing with hadron components of composite states, it was found in Ref. [29] that the sizes are bigger than expected, and components around 1 fm are not negligible. The other comment is that one should not be so strict in associating R to a size.…”
Section: A υ(4s) Statementioning
confidence: 99%
“…Then two comments are in order: the first one is that when dealing with hadron components of composite states, it was found in Ref. [29] that the sizes are bigger than expected, and components around 1 fm are not negligible. The other comment is that one should not be so strict in associating R to a size.…”
Section: A υ(4s) Statementioning
confidence: 99%
“…It was extended further to the charm-bottom system and double-bottom systems in Refs. [203,204] c D( * ) were explored in Ref. [205] and it was found that a doubly-charmed state, Ξ * cc (4380), exists with almost the same mass as P c (4380).…”
Section: B Heavy Meson-baryon Molecules Vs Doubly Heavy Baryonsmentioning
confidence: 99%
“…Its SU (3) partners, Ξ + cc and Ω + cc , are also searched for by LHCb, but with no sign of observation yet [256][257][258]. Theoretically, an important question is to understand the mass spectrum of the doubly charm baryons and related systems, which depends on the binding energy between the two heavy quarks [259][260][261][262][263][264][265][266][267][268][269][270][271]. The success discovery of Ξ ++ cc has triggered wide theoretical work to understand the properties of baryons with more than a heavy quark .…”
Section: Doubly Heavy Hadronsmentioning
confidence: 99%